Transatlantic Monetary and Fiscal Policy Interaction - Bas van Aarle; Harry Garretsen; Florence Huart (Center for Economic Studies and ifo Institute (CESifo), 2003)
This paper studies the design, effects and interactions of monetary and fiscal policies in the euro-area and between the euro-area and the non euro-area. To do so, a stylized three-country model of monetary and fiscal policy rules is constructed. It is analyzed how monetary and fiscal rules affect the adjustment dynamics in the individual euro-area countries, the aggregate euro-area and the US, which is used as a proxy of the non euro-area. Four aspects play an important role in the analysis: (i) the consequences of alternative monetary and fiscal policy rules, (ii) transatlantic spillovers and policy interactions, and the dynamics of the euro and euro-area current account, (iii) the consequences of asymmetries between euroarea countries -asymmetries in macroeconomic shocks, macroeconomic structures or policy preferences-, and between the euro-area and the US, (iv) the role of alternative degrees of backward and forward looking (expectations) in output and inflation.
Keywords: F31; F41; G15; 330; EMU; fiscal policy; monetary policy